Biodiversity maintenance may be lower under partial niche differentiation than under neutrality. Issue 12 (8th November 2017) - D'Andrea, Rafael; Ostling, Annette
Abstract: Niche differentiation is normally regarded as a key promoter of species coexistence in competitive systems. One might therefore expect that relative to neutral assemblages, niche‐differentiated communities should support more species with longer persistence and lower probability of extinction. Here we compare stochastic niche and neutral dynamics in simulated assemblages, and find that when local dynamics combine with immigration from a regional pool, the effect of niches can be more complex. Trait variation that lessens competition between species will not necessarily give all immigrating species their own niche to occupy. Such partial niche differentiation protects certain species from local extinction, but precipitates exclusion of others. Differences in regional abundances and intrinsic growth rates have similar impacts on persistence times as niche differentiation, and therefore blur the distinction between niche and neutral dynamical patterns—although niche dynamics will influence which species persist longer. Ultimately, unless the number of niches available to species is sufficiently high, niches may actually heighten extinction rates and lower species richness and local persistence times. Our results help make sense of recent observations of community dynamics, and point to the dynamical observations needed to discern the influence of niche differentiation.